Life-threatening hemorrhage following subcutaneous heparin therapy - Jana Hudcova; Daniel Talmor (Dove Medical Press, 2008)
Jana Hudcova, Daniel TalmorDepartment of Anesthesia, Critical Care and Pain Medicine, Beth Israel Deaconess Medical Center and Harvard Medical School, Boston, MA, USAAbstract: Prophylactic administration of unfractionated heparin is a common practice in a perioperative period. Heparin monitoring with subcutaneous dosing is not recommended; however it becomes important in selected patients. We report a case of massive hemorrhage with subcutaneous heparin administration in an HIV-positive male patient with cachexia and mild liver dysfunction. Prolonged activated plasma thromboplastin time and thrombin time, but normal reptilase time well as response to protamine sulfate point towards the heparin effect. Inhibitor screen was negative and factor VIII activity was normal. All these rule out the possibility of acquired factor VIII inhibitor or any other inhibitor and confirm that this bleeding was due to heparin overdose. We believe that delayed clearance of UH secondary to possible involvement of reticuloendothelial system might have been be responsible for heparin overdose even though inadvertent administration of large dose of heparin intravenously can not be completely ruled out. Administration of unfractionated heparin to a patient with cachexia and abnormal liver function warrants close attention to heparin monitoring or switch to low molecular weight heparin since its mechanism of elimination differs.Keywords: unfractionated heparin, bleeding, prophylaxis, liver dysfunction, cachexia, HIV